Quirópteros da Estação Ecológica da Serra das Araras, Mato Grosso, Brasil, com o primeiro registro de Artibeus gnomus e A. anderseni para o cerrado - Gonçalves, Edmara [UNESP]; Gregorin, Renato (My University, 2004)
We present the results of the first bat inventory at the 'Serra das Araras' Ecological Station, MT, in the northwestern portion of the Cerrado domain. We captured bats using the traditional ground-level mist netting and, occasionally, high nets placed 3 m above the ground, and hand nets for hoosting bats. We recorded 23 species distributed in six families (Emballonuridae, Noctilionidae, Mormoopidae, Phyllostomidae, Molossidae, and Vespertilionidae), including Artibeus gnomus and A. anderseni, which had never been recorded in the Cerrado domain. © 2004 Instituto de Ciências Biológicas - UFMG.
Bats of the 'Serra das Araras' Ecological Station, Mato Grosso state, Brazil, with the first records of Artibeus gnomus and A. anderseni for the cerrado
Keywords: Brazilian Cerrado; Chiroptera; Faunistic inventory; Serra das Araras Ecological Station; bat; new record; species inventory; Brazil; Mato Grosso; South America; Western Hemisphere; World; Artibeus anderseni; Artibeus glaucus gnomus; Caesalpinia ciliata; Emballonuridae; Molossidae; Mormoopidae; Noctilionidae; Phyllostomidae; Vespertilionidae